The mayfly nymph Austrophlebioides pusillus Harker defies common osmoregulatory assumptions. Issue 1 (January 2017) - Dowse, Renee; Palmer, Carolyn G.; Hills, Kasey; Torpy, Fraser; Kefford, Ben J.
Abstract : Osmoregulation is a key physiological function, critical for homeostasis. The basic physiological mechanisms of osmoregulation are thought to be well established. However, through a series of experiments exposing the freshwater mayfly nymph Austrophlebioides pusillus (Ephemeroptera) to increasing salinities, we present research that challenges the extent of current understanding of the relationship between osmoregulation and mortality. A. pusillus had modelled 96 h LC10, LC50 and LC99 of 2.4, 4.8 and 10 g l −1 added synthetic marine salt (SMS), respectively. They were strong osmoregulators. At aquarium water osmolality of 256 ± 3.12 mmol kg −1 (±s.e.; equivalent to 10 g l −1 added SMS), the haemolymph osmolality of A. pusillus was a much higher 401 ± 4.18 mmol kg −1 (±s.e.). The osmoregulatory capacity of A. pusillus did not break down, even at the salinity corresponding to their LC99, thus their mortality at this concentration is due to factors other than increased internal osmotic pressure. No freshwater invertebrate has been previously reported as suffering mortality from rises in salinity that are well below the iso-osmotic point. Recently, studies have reported reduced abundance/richness of Ephemeroptera with slightly elevated salinity. Given that salinization is an increasing global threat to freshwaters, there is an urgent need for studies into the osmophysiology of the Ephemeroptera to determine if their loss at locations with slightly elevated salinity is a direct result of external salinity or other, possibly physiological, causes.